Molecular distribution of biocide resistance genes and susceptibility to biocides among vancomycin resistant Staphylococcus aureus (VRSA) isolates from intensive care unit (ICU) of cardiac hospital- A first report from Pakistan - Muhammad Umer Asghar; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq (Heliyon, 2023)
Background: The study was conducted with the aim to investigate the VRSA isolates in terms of their susceptibility to routinely used biocides influenced by the co-occurrence of biocide resistant gene (BRGs) and efflux pumps genes. Methodology: Frequently touched surfaces within intensive care unit (ICU) of cardiac hospital were classified into three primary sites i.e., structure, machines and miscellaneous. Over a period of six months (January 2021 to July 2021) twenty three swabs samples were collected from these sites. Subsequently, these samples underwent both phenotypic and molecular methods for VRSA isolation and identification. Susceptibility and efficacy testing of biocides (benzalkonium chloride (BAC), cetrimide (CET) and chlorhexidine gluconate (CHG)) were evaluated using microdilution broth and suspension method. Furthermore, specific primers were used for singleplex PCR targeting BRGs (cepA, qacA, and qacE) and efflux pump (norA, norB, norC, sepA, mepA and mdeA) associated genes. Results: We found that 72.2 % S. aureus demonstrate the presence of vanA or vanB genes with no significant difference among three sites (p > 0.05). cepA is the most dominant BRGs followed by qacA and qacE from structure site as compared to other sites (p < 0.05). BAC showed reduced biocide susceptibility and MIC50. There was no significant difference between presence or absence of BRGs and high MIC values of VRSA isolates from all three sites. However, efflux pump genes (EFPGs) particularly norA and norA + sepA had a significant association with BRGs and reduced biocide. Conclusion: BAC is the most effective disinfectant against VRSA. Proper and controlled use of BAC is required to overcome the VRSA contamination. We recommend continuous monitoring of the BRGs prevalence for better prevention of microorganism dissemination and infection control in hospitals.